Recycled aggregate concrete at elevated temperatures - Çelik, Bülent. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Recycling the demolished concrete as aggregate and reuse of the recycled aggregates in concrete can help to prevent environmental pollution and keep the natural resources. However, fresh and hardened properties of concretes produced with these recycled aggregates must be guaranteed. This study presents the effects of elevated temperatures on mechanical and durability properties of recycled aggregate concretes. Concrete and other construction materials sometimes exposed to elevated temperatures. Concrete mixtures containing recycled coarse aggregates in amounts of 25, 50, 75, and 100 percent were prepared. Test specimens were exposed to elevated temperatures up to 250 0C. After exposure, the mechanical properties were determined using compressive strength, static modulus of elasticity and splitting tensile strength tests, while the durability properties were investigated through the permeability tests, such as with water absorption, rapid chloride permeability, sorptivity, and mercury intrusion porosimetry (MIP) tests, and crack pattern observations and porosity measurements by image analysis on micrographs taken through scanning electron microscope (SEM). The effect of the source concrete quality, water cement ratio, replacement ratio, exposure temperature level and age were examined. The effect of source concrete quality was not found to be significant, while the most significant factor affecting the mechanical and durability properties was found as water/cement ratio. Recycled aggregate content influenced the durability properties much more than the mechanical properties. In general the age factor has a positive effect on measured properties, whereas the elevations in temperatures ranging from room temperature to 250 0C indicated different patterns. The effect of elevated temperatures on the durability properties of concrete was more pronounced for concrete mixtures produced with recycled aggregates than normal concretes. Ten percent replacement of natural aggregate by recycled aggregate assured to retain mechanical and durability properties of concretes after elevated temperatures.
Keywords: Aggregates (Building materials) -- Recycling.; Concrete -- Recycling.